Techniques to Avoid Shifting to The Mother Tongue When Teaching Using EFL As The Language of Instruction - Bagas Prayogo Utomo; Tono Suwartono (Universitas Muhammadiyah Jember, 2020)
Learning other language is not just translating ideas into the targeted language, but it is an act of learning the whole set of the language itself. In the context of teaching English as a Foreign Language, teachers take very crucial role. They should be able to set such atmosphere where their students can be exposed into English environment as much as possible. On the other hand, maintaining the use English at all time is a difficult task to do, since the vocabulary of the foreign learners, often, is very limited. It creates a challenge for the teacher, in terms of making the students comprehend a certain word that they do not understand previously. Shifting into the mother tongue is surely the easiest escape from this matter. However, a teacher should be creative enough to find alternatives that allow the students to learn new words while the use of English is maintained. There are techniques that a teacher can use to provide comprehension to the students without shifting into the mother tongue.